TINJAUAN HUKUM PROSES PERALIHAN HAK MILIK ATAS TANAH JIKA AHLI WARIS PENJUAL MENOLAK MENANDATANGANI AKTA JUAL BELI - Chindi Fatika Putri; Susilowardani, Susilowardani; Yudhi Widyo Armono (Journal of Innovation Research and Knowledge, 2025)
The purpose of this study is to find out the legal procedures that govern the transfer of land rights due to inheritance, as well as the dispute resolution mechanism that arises due to the rejection of the signature of the heirs. This research uses a research method in the form of an empirical juridical approach. This research uses data collection techniques in the form of interviews with related parties including notaries/PPAT and land officials and is equipped with data collection techniques with literature studies. The result of this study is that the refusal of the heirs can hinder the process of changing the name of the land certificate administratively. Therefore, the settlement of disputes against the refusal can be carried out by submitting a lawsuit to the court, then the judge's decision that has legal force can still be used as a legal basis to continue the land registration process at the National Land Agency. Thus, the court has an important role in ensuring legal certainty in the transaction of buying and selling inherited land